Pengaruh Penambahan Sari Lengkuas Merah (alpinia purpurata k. Schum) dan Lama Simpan Telur Asin Terhadap Total Mikroorganisme, Aktivitas Antioksidan, Aktivitas Air dan Tekstur (Jurnal Ilmu dan Teknologi Hasil Ternak, 2015)
The purpose of this research was to determine the best concentration of red galangal extract and different storage in salted egg in terms of total microorganism, antioxidant activity, water activity and texture of egg salted. The materials were duck’s egg, water, salt, and red galangal extract. The method of this research was experiment with Nested Design by using two factors, namely concentrations of treatment were P0 (0%) and P1 (40%) and storage period were H0 (Day 0), H5(Day 5), H10 (Day 10), H15 (Day 15) by using five times replication. The result showed that the the addition of red galangal exract 40% gave the best result and quality of salted egg total organism 3.418, antioxidant activity 125.960 mg/g, water activity in albumen 0.949, water activity in yolk 0.931, texture in albumen 6.86, texture in yolk 11.19 with the best storage was period 0 days.